Neurological outcomes of untreated brainstem cavernous malformations in a prospective observational cohort and literature review. Issue 4 (18th March 2021) - Li, Da; Zheng, Jing-Jie; Weng, Jian-Cong; Liu, Pan-Pan; Wu, Ze-Yu; Zhang, Li-Wei; Zhang, Jun-Ting; Wang, Liang; Wu, Zhen
Abstract : Background: Haemorrhages of brainstem cavernous malformations (CMs) can lead to neurological deficits, the natural history of which is uncertain. The study aimed to evaluate the neurological outcomes of untreated brainstem CMs and to identify the adverse factors associated with worsened outcomes. Methods: From 2009 to 2015, 698 patients (321 women) with brainstem CMs were entered into the prospective cohort after excluding patients lost to follow-up (n=43). All patients were registered, clinical data were collected and scheduled follow-up was performed. Results: After a median follow-up of 60.9 months, prospective haemorrhages occurred in 167 patients (23.9%). The mean modified Rankin Scale scores at enrolment and at censoring time were 1.6 and 1.2. Neurological status was improved, unchanged and worsened in 334 (47.9%), 293 (42.0%) and 71 (10.2%) patients, respectively; 233 (33.4%) recovered to normal levels. Lesions crossing the axial midpoint (relative risk (RR) 2.325, p=0.003) and developmental venous anomaly (DVA) (RR 1.776, p=0.036) were independently significantly related to worsened outcomes. The percentage of worsened outcomes was 5.3% (18 of 337) in low-risk patients (neither DVA nor crossing the axial point) and increased to 26.0% (13 of 50) in high-risk patients (with both DVA and crossing the axial point). The percentage of worsened outcomes significantly increased as the number of prospective haemorrhages increased (from 1.5% (8 of 531, if 0 prospective ictus) to 37.5% (48 of 128, if 1 ictus) and 38.5% (15 of 39, if >1 ictus)). Conclusions: The neurological outcomes of untreated brainstem CMs were improved/unchanged in majority of patients (89.8%) with a fatality rate of 1.7% in our cohort, which seemed to be favourable. Radiological features significantly predicted worsened outcomes. Our results provide evidence for clinical consultation and individualised treatment. The referral bias of our cohort was underlined.